Is there a correlation in frontal plane knee kinematics between running and performing a single leg squat in runners with patellofemoral pain syndrome and asymptomatic runners? - Rees, D.; Younis, A.; MacRae, S. (Clinical Biomechanics, 2019)
Knee kinematics when running, specifically knee valgus, have been linked to patellofemoral pain syndrome. Assessing running biomechanics requires skill, equipment and time. Clinically, the single leg squat is used to make inferences about knee kinematics during running. No evidence supports this practice. Methods